Scratch na produção de recursos interdisciplinares com disciplinas indígenas - Rabêlo, Hévellyn; de Oliveira, Wênnio; Santos, Luan; de Araújo, Ana Liz; Souza, Flávia (Anais do Workshop sobre Educação em Computação (WEI); 2015: Anais do XXIII Workshop sobre Educação em ComputaçãoDO - 10.5753/wei.2015.10218, 2015)
Integrate computation at primary education is a current challenge. This work is an initiative that provides planning, implementation and evaluation of a course that integrate computational thinking by programming in Art and Culture and Tupi Language disciplines at Indian schools. Scratch was used to produce animations in the contents of indigenous culture. The animations were evaluated by a framework to measure the computational thinking with Scratch code.